2005
DOI: 10.1007/s00436-005-1368-9
|View full text |Cite
|
Sign up to set email alerts
|

Genotype of Giardia intestinalis isolates from children and dogs and its relationship to host origin

Abstract: The presence of human Giardia in several animals suggests a zoonotic transmission. We studied G. Intestinalis isolates obtained from: children with diarrhea (n=6), asymptomatic children (n=7), axenic cultures (n=7) and dogs (n=11). The sequence corresponding to 16 S rRNA was amplified by PCR, sequenced and compared with genotypes A, B and Dog sequences reported in the Gene Bank database. Results show that 9/20 (45%) of children isolates belonged to genotype A and 11/20 (55%) showed some variable sites, allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 28 publications
2
27
1
Order By: Relevance
“…These transmission cycles reflect the close association shared Page 14 of 31 A c c e p t e d M a n u s c r i p t 14 between dogs and humans, as well as the close interaction shared between dogs as pack animals in these Temple communities, which is expected in urban environments (Itagaki et al, 2005). There was however, an unusual dominance of Assemblage A genotypes of G. duodenalis in dogs as well as in humans in our study, supporting a number of previous studies (Traub et al, 2004;Eligio-Garcia et al, 2005;Itagaki et al, 2005;Lalle et al, 2005) indicating that Assembalge A may be most significant genotype when dealing with zoonotic potential. Dog-specific Assemblages C and D of G. duodenalis were also recovered from a moderate number of humans in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These transmission cycles reflect the close association shared Page 14 of 31 A c c e p t e d M a n u s c r i p t 14 between dogs and humans, as well as the close interaction shared between dogs as pack animals in these Temple communities, which is expected in urban environments (Itagaki et al, 2005). There was however, an unusual dominance of Assemblage A genotypes of G. duodenalis in dogs as well as in humans in our study, supporting a number of previous studies (Traub et al, 2004;Eligio-Garcia et al, 2005;Itagaki et al, 2005;Lalle et al, 2005) indicating that Assembalge A may be most significant genotype when dealing with zoonotic potential. Dog-specific Assemblages C and D of G. duodenalis were also recovered from a moderate number of humans in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Recent literature has focussed on the role of companion animals as providing the greatest risk of zoonotic transmission of G. duodenalis ( Traub et al, 2004;Eligio-Garcia et al, 2005;Itagaki et al, 2005;Lalle et al, 2005). This conclusion has largely been drawn from data showing that G. duodenalis is one of the most common enteric parasites of dogs in both developed as well as disadvantaged communities worldwide (Itoh et al, 2001;PonceMacotela et al, 2005) and that genetically identical, potentially zoonotic genotypes of G. duodenalis (predominantly Assemblage A) may exist in humans and dogs living within the same locality (Ponce-Macotela et al, 2002;Traub et al, 2004;Eligio-Garcia et al, 2005;Lalle et al, 2005) . On the other hand, non-zoonotic or dog-specific cycles of G. duodenalis transmission have also been shown to exist in dogs in communities where it is hypothesised that the frequency of transmission of Giardia among dogs is high (Hopkins et al, 1997;Itagaki et al, 2005;Palmer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers in Europe, Asia and South America have found a correlation between genotype and symptomatology, while other authors have observed no association [8,37,49,56,92,[104][105][106][107][108]. Both Giardia genotypes (A and B) are capable of causing symptomatic infection in humans, and the same genotype has been reported in different sets of clinical signs [101,109].…”
Section: Genotype-clinical Presentation Relationshipmentioning
confidence: 97%
“…Recently, some investigators have proposed species-specific names for the different genotypes of G. duodenalis [ Table-1] [40,41]. Genotypes A and B of G. duodenalis have been the only genotypes involved in human infection [2,8,10,42].…”
Section: Molecular Epidemiology Of Giardiamentioning
confidence: 99%
“…The occurrence of children presenting G. duodenalis that had pets at home was low, and in no one case pets were suspect to be the source of contamination, given that they did not present G. duodenalis cysts. Nevertheless, the zoonotic transmission between dogs and children may also occur 6 .…”
Section: Discussionmentioning
confidence: 99%